Whole Genome Analysis of Pediococcus acidilactici XJ-24 and Its Role in Preventing Listeria monocytogenes ATCC® 19115TM Infection in C57BL/6 Mice - Weizhong Hu; Shuxin Zhou; Amel Ibrahim; Guannan Li; Sameh Awad; José Ramos-Vivas; Jianquan Kan; Muying Du (Antibiotics)
Background/Objectives: As probiotics gain prominence in the prevention and treatment of intestinal diseases, their protective effects against pathogens and influence on host health have drawn significant attention. This study investigates the genomic characteristics and functional potential of Pediococcus acidilactici XJ-24 (XJ-24) in the prevention of Listeria monocytogenes (LM) infection in mice. Methods/Results: Whole-genome analysis confirmed the safety and probiotic properties of XJ-24, including acid and bile salt tolerance, antimicrobial activity, and safety. In vivo, C57BL/6 mice challenges indicated that XJ-24 significantly reduced LM colonization, suppressed pro-inflammatory cytokines (IL-1β, IL-6, TNF-α, IFN-γ), alleviated colon and spleen tissue damage, and maintained intestinal barrier integrity by upregulating tight junction proteins (Occludin, Claudin-1, ZO-1). Moreover, XJ-24 modulated gut microbiota composition by increasing beneficial taxa while reducing harmful bacteria. Correlation analysis highlighted a positive association between Lachnospiraceae and tight junction proteins. Conclusions: These findings demonstrate the potential of XJ-24 as a functional probiotic for preventing LM infection and provide a basis for further clinical exploration.